Subpolar addition of new cell wall is directed by DivIVA in mycobacteria - Meniche, Xavier (National Academy of Sciences, 2014)
Mycobacteria are surrounded by a complex multilayered envelope and elongate at the poles. The principles that organize the coordinated addition of chemically diverse cell wall layers during polar extension remain unclear. We show that enzymes mediating the terminal cytosolic steps of peptidoglycan, arabinogalactan, and mycolic acid synthesis colocalize at sites of cell growth or division. The tropomyosin-like protein, DivIVA, is targeted to the negative curvature of the pole, is enriched at the growing end, and determines cell shape from this site. In contrast, cell wall synthetic complexes are concentrated at a distinct subpolar location. When viewed at subdiffraction resolution, new peptidoglycan is deposited at this subpolar site, and inert cell wall covers the DivIVA-marked tip. The differentiation between polar tip and cell wall synthetic complexes is also apparent at the biochemical level. Enzymes that generate mycolate precursors interact with DivIVA, but the final condensation of mycolic acids occurs in a distinct protein complex at the site of nascent cell wall addition. We propose an ultrastructural model of mycobacterial polar growth where new cell wall is added in an annular zone below the cell tip. This model may be broadly applicable to other bacterial and fungal organisms that grow via polar extension.